2014
DOI: 10.1039/c4ce00989d
|View full text |Cite
|
Sign up to set email alerts
|

CuII–PDC-bpe frameworks (PDC = 2,5-pyridinedicarboxylate, bpe = 1,2-di(4-pyridyl)ethylene): mapping of herringbone-type structures

Abstract: This work explores new metal–ligand combinations to produce flexible SCFs based on 3-c herringbone layers. The work analyses this type of layers, and provides correlation tools for the structural parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…The interest of the present work lies on the fact that, as previously said, it first explores the PDC-bpa combination. The change from bpe [39] to bpa (current work) results in flexible herringbone-type SCFs related by a phase transformation. On the other hand, the lack of reversibility for this transformation is coherent with the fact that one of the compounds is the closest one to ideal 3-c herringbone-type arrangement reported so far.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The interest of the present work lies on the fact that, as previously said, it first explores the PDC-bpa combination. The change from bpe [39] to bpa (current work) results in flexible herringbone-type SCFs related by a phase transformation. On the other hand, the lack of reversibility for this transformation is coherent with the fact that one of the compounds is the closest one to ideal 3-c herringbone-type arrangement reported so far.…”
Section: Introductionmentioning
confidence: 94%
“…The new solids are related to Cu-PDC-bpe compounds published by us elsewhere [39] where bpe is 1,2-di(4-pyridyl)ethylene). In that article we first established the different nature of the 4-c and 3-c herringbone arrays, and did identify the structural features for the 3-c ones.…”
Section: Introductionmentioning
confidence: 99%
“…In all studies isonicotinamide coordinates to the copper(II) ion in a monodentate form through the pyridine N atom or in a bidentate one [16] thus providing possibilities for polymeric coordination networks. Pyridine-2,5-dicarboxylic acid combines the advantages of both organic multicarboxylic acids and heteroaromatic compounds and displays versatile coordination modes through its one N atom and four carboxylate O atoms, which in alliance with Cu(II) leads to the formation of coordination homometallic [23][24][25][26][27] and/or heterometallic [26,[28][29][30] polymers. With that in mind, in this contribution, we intended to extend the dimensionality of a new coordination compound obtained by the combination of isonicotinamide with pyridine-2,5-dicarboxylate ligands.…”
Section: Introductionmentioning
confidence: 99%
“…The retrieval of Cambridge Structural Database (CSD) revealed that the combination of Cu(II) with isonicotinamide resulted in structural diversity, including mono- [13][14][15], binuclear [14,[16][17][18], 1D [7,16,[19][20][21] and 2D polymeric arrays [7,22,23]. In all studies isonicotinamide coordinates to the copper(II) ion in a monodentate form through the pyridine N atom or in a bidentate one [16] thus providing possibilities for polymeric coordination networks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation